THE MODERN TRENDS OF DEVELOPMENT OF STANDARDIZATION OF THE REQUIREMENTS TO EDUCATIONAL ICT TOOLS - Y. Zaporozhchenko (Kherson State University, 2012)
The article presents current trends of informational and educational environment development in terms of defining and standardization of the requirements to educational ICT, use of prospective technologies and innovative approaches to the implementation of e-learning systems. The problems of implementing of quality management methodology in a sphere of high-tech products, as well as future prospects of development of e-learning tools are outlined.